PENGARUH MARKET TIMING THEORY TERHADAP STRUKTUR MODAL PERUSAHAAN NON-KEUANGAN DI INDONESIA - , ANANDA MEITA TAURISINA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aimed to examine the effect caused by market timing theory of the companyâs capital structure on the non-financial sector in Indonesia. Philosophy of market timing refers to the activities of issuing shares at a high price and buy it back at a low price (equity market timing). The sample of this study was 48 non-financial companies that IPO in the period 2008-2010. Authors used multiple regression analysis model to determine the effect of leverage and the changes leverage as dependent variables to the market to book and the highest market to book since IPO as independent variables. Furthermore, the control variables also used of which is profitability, firm size, and liquidity. The results of this study found a positive effect of the market to book on the previous year to the leverage. But for the highest market to book in the past of the company since IPO proved negative significant to the leverage. It can be concluded that the ratio of market to book in the past still influence the decision of corporate funding in subsequent years. However, the ratio of market to book on the previous year does not necessarily affect the company to increase its equity, as it utilized to increase the debt.